Dra' Abu el-Naga, Ägypten. Das thebanische Pauloskloster (Deir el-Bachît). Sakraltopographie einer Klosterlandschaft und ihre Entwicklung auf dem Hügel von Dra' Abu el-Naga/Oberägypten. Die Arbeiten der Jahre 2016 und 2017 - Eichner, Ina (e-Forschungsberichte des DAI, 2017)
The work undertaken in autumn 2016 and spring 2017 in the Monastery of St. Paulos (Deir el-Bakhît) focused on the so-called main monastery (late 6th/early 7th century AD to the beginning of the 10th century AD), a compact coenobitic monastery complex which, however, constitutes one of three monastic complexes that were in use on the hill of Dra' Abu el-Naga. A newly granted project will explore questions on the social status and the hierarchy of the monks, the organisation and the hierarchical relationship between the three interconnected but functionally different complexes on the hill as well as the political influences on the development of this unique monastic landscape and sacral topography.